Comparison of spark plasma and microwave sintering of mullite based composite: Mullite/Ta2O5 reaction. Issue 11 (1st August 2018) - Derakhshandeh, S.M.R.; Gohari, M. Sirati; Saeidabadi, E. Karimi; Jam, A.; rajaei, H.; Fazili, A.; Alizadeh, M.; Ghasali, E.; Pakseresht, AH.; Ebadzadeh, T.
Abstract: In this study, mullite ceramic matrix composites (CMCs) reinforced with Ta2 O5 particles (10 wt%) were fabricated through spark plasma sintering (SPS) and microwave sintering (MW) methods. The prepared batches were sintered at 1200 °C and 1300 °C in SPS method. The composite was also sintered at 1300 °C by MW method. In SPS, in order to achieve maximum densities, the sintering temperature increased so that the maximum displacements maintain in each sample. By reaching the temperature to 1200 °C in SPSed sample, the punch displacement stopped, while at 1300 °C in the same sample, it occurred at 1300 °C. The results showed that a high enough density was achieved in SPS sintered samples, while the MW sintered sample revealed higher amounts of porosities (23.81 ± 0.08%) and water absorption (12.20 ± 0.08%) together with low bulk density (2.562 ± 0.003 g/cm 3 ). The values of apparent density, porosity, and water absorption of the SPS sintered sample at 1200 °C were obtained as 3.283 ± 0.002 g/cm 3, 2.38 ± 0.05% and 1.02 ± 0.04%. Also, these values for the SPSed sample at 1300 °C were 3.301 ± 0.001 g/cm 3, 1.53 ± 0.03% and 0.48 ± 0.05%, respectively. The higher punch displacement, higher bulk density, lower porosity and water absorption of the SPSed sample at 1300 °C might be due to the higher sintering temperature, which causes the reduction of porosities alongside the increase in the probable reactions between the mullite and Ta2 O5 phases. The XRD and FESEM investigations revealed the formation of AlTaO4 phases at mullite/Ta2 O5 boundaries. It was also proved that increasing the sintering temperature has a significant effect on AlTaO4 phase formation. The SPSed sample at 1200 °C obtained the maximum bending strength of 329 ± 31 MPa in comparison to the sample sintered at 1300 °C (228 ± 26 MPa).